The wage-penalty effect: the hidden cost of maternity leave - Baker, D (The Australia Institute, 2011)
In 2011, the introduction of a Paid Parental Leave Scheme saw Australia catch up with other developed countries, including New Zealand where a similar scheme had been in place for a decade. The Australian scheme is means-tested and provides employed parents with the option of 18 weeks’ PPL at the minimum wage. While the new scheme provides 18 weeks’ income at the minimum wage, it does not address the wage penalty that can be experienced when parents, often women return to work following parental leave. Analysis of the Household, Income and Labour Dynamics in Australia (HILDA) survey reveals that, in the first year back at work, a wage penalty of just over four per cent exists for women in Australia, which equates to more than three weeks of PPL payments under the new scheme. The ‘wage-penalty’ effect increases over the next two years. The paper concludes with possible policies to address the financial implications of a wage penalty, and the factors influencing this phenomenon.
The wage-penalty effect: The hidden cost of maternity leave
Keywords: Employment; Employment -- Parental leave; Policy; Finance -- Income (Salary and Wages); Policy -- Parenting; Finance; Government, law and policy; Income, wealth and finances; Labour market; Employment; Policy; Finance; Income (Salary and Wages); Parenting; Parental leave; Employment and unemployment; Government, law and policy; Income, wealth and finances